Implementation of multicultural education perspective based on Islamic values facing the post-truth era in sociology social studies learning - Arifansyah, Jamal; Suswandari, Suswandari; Bandarsyah, Desvian (Harmoni Sosial: Jurnal Pendidikan IPS, 2023)
This research aims to analyze the relationship between the harmonization of multicultural education perspectives with Islamic values, implement a multicultural education model based on Islamic values in sociology learning, and analyze the success of the implementation of multicultural education perspectives based on Islamic values in facing the post-truth era. This research uses a qualitative research design with a case study approach. Data was collected using in-depth interview techniques with key informants, namely the vice principal for curriculum, the sociology subject teacher of class XI IPS, and several students of class XI IPS. Observations were conducted in and outside the classroom and in several school activities and documentation studies. Data analysis techniques include pattern matching, explanation making, and time series analysis. The research instrument was validated through the triangulation method and data sources. The results showed that the harmonization of Islamic values-based multicultural education perspectives at Al Azhar 4 Islamic High School is based on the principles of tolerance and equality manifested in the culture of smiles, greetings, cultural festivals, inter-school competitions, and community empowerment social services.